Laser-Induced Breakdown Spectroscopy (LIBS) of a High-Pressure CO2–Water Mixture: Application to Carbon Sequestration. Issue 9 (September 2014) - Goueguel, Christian; McIntyre, Dustin L.; Singh, Jagdish P.; Jain, Jinesh; Karamalidis, Athanasios K.
Geologic carbon storage in deep saline aquifers is considered a feasible and possible approach of mitigating the problem of increasing greenhouse gas emissions. However, there are latent risks in which carbon dioxide (CO2 ) could migrate from the deep saline formations to shallower aquifers. In the event of a significant CO2 leakage to an underground source of drinking water, CO2 will dissolve in the water, thereby increasing its acidity, which could potentially enhance the solubility of various aquifer constituents, including hazardous compounds, subsequently compromising groundwater quality due to increased concentration of aqueous metals. In this paper we explore the possibility of detecting such leakage by the use of laser-induced breakdown spectroscopy (LIBS). The experiments were conducted in calcium chloride solution at three pressures of 10, 50, and 120 bar. To evaluate the direct effect of elevated CO2 on the intensity of calcium emission lines (422.67 and 393.37 nm), we also performed experiments with pure nitrogen (N2 ) gas, offering large water solubility contrast. We found that when performed in presence of CO2, LIBS showed only a modest decrease in Ca emission intensity from 10 to 120 bar compared to N2 . These results indicate that LIBS is a viable tool for measuring brine/water contents in high-pressure CO2 environment and can be applied for monitoring CO2 leakage and displaced brine migration.